Frequency of Types of Jejunoileal Atresia among Neonates Presenting With Intestinal Obstruction: Jejunoileal Atresia among Neonates - Majid, Fatima; Aslam, Sana; Anwar, Muhammad; Ghaffar, Misbah Abdul; Ahmed, Yasir; Nazar, Fareeha (Pakistan Journal of Health Sciences, 2025)
Jejunoileal Atresia (JIA) is a significant cause of neonatal intestinal obstruction, accounting for a substantial number of surgical emergencies in the first weeks of life. It results from congenital occlusion of the intestinal lumen, primarily due to intrauterine vascular accidents. Despite improvements in surgical techniques and neonatal care, early diagnosis and intervention remain critical for favorable outcomes. Objective: To determine the frequency of common types of jejunoileal atresia among neonates presenting with intestinal obstruction. Methods: This descriptive cross-sectional study was conducted at the Department of Paediatric Surgery, National Institute of Child Health (NICH), Karachi, from November 16, 2019, to May 15, 2020. A total of 97 neonates diagnosed with intestinal obstruction and meeting the inclusion criteria were enrolled. Detailed history, antenatal workup, and clinical examination were recorded. Diagnosis was confirmed intraoperatively, and types of JIA were documented. Results: The mean age at presentation was 5.78±4.24 days. Among the 97 neonates, 42 (43.3%) were male and 55 (56.7%) were female. The distribution of JIA types was as follows: Type I in 20 cases (20.6%), Type II in 11 cases (11.3%), Type IIIa in 45 cases (46.4%), Type IIIb in 10 cases (10.3%), and Type IV in 11 cases (11.3%). Conclusions: Type IIIa was identified as the most frequent type of jejunoileal atresia. Early recognition and surgical management are essential to reduce morbidity, mortality, and length of hospital stay in affected neonates.